VALIDITAS E-MODUL BERBASIS DISCOVERY LEARNING UNTUK KELAS XI SMA/MA - Adela Samhoriasti; Annika Maizeli; Evrialiani Rosba (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a discovery learning-based e-module on the human digestive system for Phase F students of grade XI SMA/MA. The background of this research is the limited availability and quality of teaching materials, as well as the lack of active student involvement in the learning process. In addition, the digestive system material contains abstract concepts that require interactive and innovative learning media to enhance students’ understanding. Therefore, the development of a discovery learning-based e-module is expected to support student-centered learning. This research employed a Research and Development (R&D) method using the 4-D model, which consists of define, design, and develop stages. The study was limited to the development stage. The subjects of this research included three validators, two biology teachers, and 30 students of grade XI at SMA Negeri 1 Painan. The instruments used were validity and practicality questionnaires, and the data were analyzed using percentage techniques.The results showed that the developed e-module achieved a validity level of 87.24% (very valid). The practicality test results showed scores of 89.77% by teachers and 93.01% by students (very practical). Thus, the discovery learning-based e-module is feasible to be used as a teaching material in biology learning.